Pediatric Imaging of the Elbow: A Pictorial Review - Vanmarsnille, Tim; Laloo, Frederiek; Herregods, Nele; Jaremko, Jacob L.; Verstraete, Koenraad L.; Jans, Lennart (Seminars in Musculoskeletal Radiology, 2021)
The elbow is a complex joint, subject to a wide range of traumatic, inflammatory, metabolic and neoplastic insults. The pediatric elbow has several diagnostic pitfalls due to the normal developmental changes in children. Knowledge of these normal variants is essential for both diagnosis and management of their elbow injuries. Radiography remains the first imaging modality of choice. Magnetic resonance imaging is excellent in evaluating lesions within the bone and soft tissues. In this pictorial essay, we provide insights into pediatric elbow imaging, show a range of entities specific to the pediatric elbow, and discuss diagnostic pitfalls that result from normal elbow growth in children.
Keywords: Magnetic resonance imaging; pediatric; elbow; trauma; normal variants